2025 Update to the Female Athlete Triad Coalition Consensus Statement Part 2: Clinical guidelines for screening, diagnosis, treatment, and return to play for adolescents and adults - Williams, N. I.; De Souza, M. J.; Misra, M.; Nattiv, A.; Joy, E.; Barrack, M.; Ricker, E. A.; Gorrell, S.; Koltun, K. J.; O`Donnell, E.; Mallinson, R. J.; Salamunes, A. C. C.; et al. (Sports Medicine, 2026)
This is the second of two publications comprising the 2025 update to the 2014 Consensus Statement on treatment and return to play guidelines on the Female Athlete Triad (Triad). This paper pairs with the 2025 Update to the Female Athlete Triad Coalition Consensus Statement Part 1: State of the Science and Introduction of a New Adolescent Model (Sports Medicine, 2025), to focus on evidence-based revisions for screening, diagnosis, treatment, and clearance and return to play. Revised recommendations for managing eating disorders (ED)/disordered eating (DE) and non-pharmacological and pharmacological treatment of bone loss and abnormal menstrual cycles are included, as are the most recent clearance and return to play recommendations, inclusive of adolescent athletes. Recent research supports the adoption of revised criteria for defining and treating energy deficiency, moving away from the concept of an energy-availability threshold. Energy deficiency-induced menstrual disturbances can be reversed with a moderate increase in food intake and modest weight gain, but restoration of menses alone is not associated with high rates of ovulation or increased ovarian steroid levels until multiple consecutive normal length menstrual cycles are achieved. Revised guidelines for the diagnosis and treatment of functional hypothalamic oligo/amenorrhea are included with guidance on the confounding effects of hyperandrogenemia. Gynecological age and psychological stress are factors impacting the individual susceptibility to the Triad. The bone health spectrum of the Triad now includes bone stress injuries. Routes of administration via epidermal patch versus oral for pharmacological treatment of low bone density are discussed. The diagnosis, treatment, and return to play approaches for adolescents with the Triad are unique compared with those employed for adults and require age-appropriate clinical guidelines. The strength of the evidence-based statements is graded using an accepted taxonomy in which randomized controlled trials and observational data are considered the highest level of evidence.